Students’ Perception Toward the Implementation of LMS (Syam-OK) in Learning Basic English Grammar - Darmas, Nur Aridha; Munir, Munir; Sofyan, Ryan Rayhana (Journal of Excellence in English Language Education, 2024)
This research aims to determine students’ perception toward the implementation of LMS (SYAM-OK) in learning Basic English Grammar for English Education students, Universitas Negeri Makassar. This research used a descriptive qualitative method. Participants in this research were students from the class of 2020. Data collection was collected by interviews. Based on the general interview results, the participants had positive perceptions of easy-to-access material, easy-to-access LMS (SYAM-OK), and easy-to-use features and negative perceptions, namely the lack of direct interaction and internet connection problems. The data results show that students show a more positive perception toward the implementation of LMS (SYAM-OK) in learning Basic English Grammar.